Permasalahan Pelaksanaan Restitusi Bagi Pelaku Tindak Pidana Perdagangan Orang - Neisa Angrum Adisti; Alfiyan Mardiansyah (Simbur Cahaya, 2019)
One of the compensation for Human Trafficking victims in human trafficking law number 21 of 2007 is restitution. Restitution is an effort that made victims of crime can return to their original condition before the occurrence of a crime even though it is certain that the condition may not return to normal. Recovery of victims' rights must be as complete as possible and must cover all aspect losses suffered by victims as a basic principle in the provision of restitution Law Number 21 of 2007 on human trafficking gives restitution’s punishment for Trafficker, there are some problems faced in the implementation restitution, One of the problems is restitution can be replaced with other criminal punishment  “confinement”. subsidiary of restitution sanctions may minimize the opportunity for the victim to obtain compensation restitution from trafficker. Because, if the trafficker cannot pay restitution, can be replaced with a criminal sanction “confinement”. Therefore, the government needs to change the rule about restitution sanctions in the legislation for the trafficker. That’s Important to change the rule about "subsidiary" restitution by requiring the trafficker to pay restitution without replacing with other criminal sanctions in the criminal law system in Indonesia.